Mayer-Rokitansky-Kuster-Hauser syndrome with gonadohypoplasia:a rare case report - M., Chandini; Ramineni, Hari Babu; Rakesh, Y.; Babu, K. Narendra; Vidyadhara, S. (International Journal of Research in Medical Sciences, 2017)
MRKH (Mayer Rokitansky Kuster Hauser) syndrome is a congenital abnormality seen in one out of 5,000 women characterized by the agenesis of the vagina, cervix, and uterus. It is also associated with kidney, bone and hearing difficulties. The ovaries are present with a normal function similar to that of a healthy reproductive woman’s by producing eggs and female hormones. Chromosomes are the normal 46xx female karyotype. We report this rare syndrome in a 26–year-old female where she had presented with complaints of absence of uterus with the absence of left kidney. She didn’t attain menarchy, secondary sexual characters are well developed. Small right ovarian follicular cyst with a rim of ovarian tissue was observed. She had undergone vaginoplasty.